2016
DOI: 10.1242/jeb.139568
|View full text |Cite
|
Sign up to set email alerts
|

Learning through the waste: olfactory cues from the colony refuse influence plant preferences in foraging leaf-cutting ants

Abstract: Leaf-cutting ants learn to avoid plants initially harvested if they prove to be harmful for their symbiotic fungus once incorporated into the nest. At this point, waste particles removed from the fungus garden are likely to contain cues originating from both the unsuitable plant and the damaged fungus. We investigated whether leaf-cutting ant foragers learn to avoid unsuitable plants solely through the colony waste. We fed subcolonies of Acromymex ambiguus privet leaves treated with a fungicide undetectable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…In addition, changes in the fungus garden that induced plant avoidance can only be detected by workers for a relatively short time (1–2 days; [22], suggesting that avoidance cues learned by the ants are no longer noticeable in the fungus garden after this period. Although we could not rule out that waste particles originating from treated leaves could still have been disposed of after the exchange of the waste chambers, thus appearing in the recently-exchanged waste chamber of treated subcolonies at T2, previous evidence suggests that the disposal of waste particles in the dump is considerably reduced after 36 h [36]. At T2, decisions made by an average of 26.85 ± 1.63 foragers per subcolony were recorded.…”
Section: Methodsmentioning
confidence: 83%
See 4 more Smart Citations
“…In addition, changes in the fungus garden that induced plant avoidance can only be detected by workers for a relatively short time (1–2 days; [22], suggesting that avoidance cues learned by the ants are no longer noticeable in the fungus garden after this period. Although we could not rule out that waste particles originating from treated leaves could still have been disposed of after the exchange of the waste chambers, thus appearing in the recently-exchanged waste chamber of treated subcolonies at T2, previous evidence suggests that the disposal of waste particles in the dump is considerably reduced after 36 h [36]. At T2, decisions made by an average of 26.85 ± 1.63 foragers per subcolony were recorded.…”
Section: Methodsmentioning
confidence: 83%
“…It is reasonable to think that soon after the ants recognize that the fungus is growing on an unsuitable plant, they remove the garden as waste. We have recently demonstrated that waste particles newly removed from the garden contain cues that enable plant recognition and cues or signals that resemble the impairment of the fungus [36]. In particular, we observed that volatiles of the waste mediated the identification of unsuitable host plants.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations